Long-term secrets to short-term trading - Williams, Larry R. (Hoboken, N.J. : John Wiley & Sons, 2012)
'Hugely popular market guru updates his popular trading strategy for a post-crisis worldFrom Larry Williams--one of the most popular and respected technical analysts of the past four decades--Long-Term Secrets to Short-Term Trading, Second Edition provides the blueprint necessary for sound and profitable short-term trading in a post-market meltdown economy. In this updated edition of the evergreen trading book, Williams shares his years of experience as a highly successful short-term trader, while highlighting the advantages and disadvantages of what can be a very fruitful yet potentially dangerous endeavor.Offers market wisdom on a wide range of topics, including chaos, speculation, volatility breakouts, and profit patterns Explains fundamentals such as how the market moves, the three most dominant cycles, when to exit a trade, and how to hold on to winners Includes in-depth analysis of the most effective short-term trading strategies, as well as the author's winning technical indicatorsShort-term trading offers tremendous upside. At the same time, the practice is also extremely risky. Minimize your risk and maximize your opportunities for success with Larry Williams's Long-Term Secrets to Short-Term Trading, Second Edition'--Provided by publisher.
Includes index.
Keywords: Commodity futures; Speculation